Peran Pendidikan Islam dalam Pembentukan Wawasan Kebangsaan di Sekolah Muhammadiyah - Haryono Haryono; Kohar Kohar; Atmi Saptarini (IHSANIKA : Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the role of Islamic Religious Education (PAI) in shaping national insight in Muhammadiyah schools in Pringsewu Regency. This study used a descriptive qualitative approach with in-depth interviews, classroom observations, and curriculum document analysis. The results indicate that the PAI curriculum in Muhammadiyah schools has successfully integrated national values, such as patriotism, unity, and interfaith tolerance. PAI teachers actively teach these values in lessons that involve discussion and reflection. However, challenges include limited teacher training and the gap between traditional education and modern technology. This study suggests the need for improved teacher training and the use of digital literacy to support more effective teaching of national values. Overall, Islamic education in Muhammadiyah schools plays a significant role in strengthening students' national insight, with opportunities for further development through the use of technology and collaboration between educational institutions.